Analysis of Factors in Decision Making of Ex-Rubber Farmers Regarding the Conversion of Rubber Plantations to Oil Palm (Case Study in Muara Jalai Village, Kampar Regency) - Hamid, Ardiansyah; Wandana, Fajar Aga (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
Logging of rubber trees is increasingly being carried out by rubber farmers in Muara Jalai Village. In fact, rubber plantations are one of the sources of community livelihoods that have long been practiced by some people. Seeing the rampant phenomenon of cutting down rubber trees in Muara Jalai Village, an in- depth study was conducted on the behavior of these ex-rubber farmers, to see how much influence the factors of rubber income, rubber maintenance and rubber sap production have on the decision to cut down rubber trees. For this reason, a questionnaire was distributed to ex-rubber farmers and a validity test was carried out on the questionnaire, the results showed that all statements from the questionnaire were valid to be used as a questionnaire. After the validity test, then proceed with the t test. The t test results show that the value of tcount> ttable for the three independent variables. It can be concluded that the independent variables of rubber income, rubber maintenance and rubber sap production affect the decision of rubber farmers to cut down rubber trees. In addition, the F test was also conducted. The results of the F test show the value of Fcount> Ftable. It can be concluded that the three independent variables all affect the decision of rubber farmers in cutting down rubber trees.